The Influence Of Knowledge And Service On Public Interest In Using Mudharobah Saving Products At Bank Kalbar Sharia Sambas Branch - Misbun; Sri Deti; Beti Yanuri Posha (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
This study departs from the public's interest in transacting in Islamic banking, one of which is from the level of knowledge and service the bank itself has for customers, the more understanding and services provided, the higher the interest in transacting at Bank Kalbar Syariah Sambas Branch with a Research Focus How does variable X1 influence (knowledge) of variable Y (intention to save) on mudharabah savings products, at Bank Kalbar Syariah Sambas Branch?. This research uses quantitative methods, including field studies. Data collection techniques through interview techniques and questionnaire surveys in the form of questionnaires were then analyzed using the classical assumption test, multicollinearity, non-autocorrelation test, and non-heteroscedasticity test. The results of the study show the following hypotheses t test (Partial), customer knowledge partially influences the intention to save, service partially influences the intention to save. Meanwhile, based on the results of the F test on the ANOVA table it shows that the F value is 854,188 with a probability value of 0,000 so < 0.05. Then F count > F table, namely 854,188 > 3,088 so based on the hypothesis used in this study H1 is accepted and H01 is rejected, H2 is accepted and H02 is rejected, and H3 is accepted and H03 is rejected thus knowledge and service of the Sambas Branch Sharia Bank Kalbar simultaneously affect interest in saving